Identifying The Functions of Serang City Square as a Public Green Space - Shinta Permana Putri; Raddina Nur Fattima (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Serang City, as the capital of Banten Province, has met the urban green open space standards, achieving a percentage of 59.64%. Serang City Square is one of the representations of public green open spaces in the area. This study aims to identify the extent to which Serang City Square fulfills its ecological, socio-cultural, aesthetic, and economic functions as a public green open space. This study is based on the direct perceptions of visitors and addresses a research gap, as perception-based evaluations of public green open spaces remain limited, particularly in the context of Serang City Square. This research is a quantitative descriptive study. Data were collected through a questionnaire survey and field observations. The questionnaire survey was conducted with 100 visitors of Serang City Square. Field observations were also carried out to complement the questionnaire data. The data were then analyzed using descriptive statistical and qualitative descriptive analysis techniques. The results indicate that Serang City Square has fulfilled most of its ecological and economic functions; however, some aspects of its social and aesthetic functions remain suboptimal. This is shown by the absence of children’s play areas, public perception of poor cleanliness and sanitation, and insufficient lighting that affects comfort and environmental aesthetics. These findings indicate the need for intervention by the Serang City Government to strengthen the functionality of Serang City Square as a public green open space.